(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
The work presents the results of the synthesis of polymer ligands based on urea, formaldehyde, and aniline via the condensation/polycondensation method, followed by modification with target functional groups. The obtained copolymers were characterized using FT-IR, 1H/13C NMR, thermogravimetry (TGA/DSC), scanning electron microscopy (SEM), and elemental analysis. The acid-base properties, density of donor centers, and complexation ability with model heavy metal ions in an aqueous medium were investigated. It was established that the synthesized materials possess high thermal stability, high functional group content, and efficient sorption/complexation performance, making them promising for applications in analytical chemistry, wastewater treatment, and as precursors for the fabrication of specific sorbents and ion exchangers. Where necessary, data on sorption kinetics and isotherms are provided.